Ushul al-Nahwi al-Arabi : Kajian Tentang Landasan Ilmu Nahwu - Rini, Rini (Institut Agama Islam Negeri (IAIN) Curup, 2019)
Nahwu is a very important science in learning Arabic because it contains Arabic rules and grammar. So far there are still many Arabic language learners who have not understood the foundation of the formation of nahwu. This article aims to examine more about the foundation of the established nahwu science. The method used in this study is the library research method, which is a series of activities relating to the method of collecting library data, reading and recording and processing research materials. The results of this study are that the nahwu rules that we have known so far are not necessarily available and available, but have been formulated with hard work and high precision by nahwu experts through four sources are the sama ', ijma’, qiyas and istishab.